A contribuição da energia solar fotovoltaica para o desenvolvimento rural sustentável - Micheletti , Danilo Hungaro (2023)
The application of new energy technologies contributes to improving agricultural activities in terms of productivity, economic performance and quality of life. Photovoltaic solar energy is a technology capable of promoting sustainable rural development, as it promotes access to clean energy and provides economic, environmental and social development. The main objective of this work was to analyze the contribution of the use of photovoltaic solar source generating systems in the sustainable development of rural properties in the municipality of Iporã–PR. The research was arranged as a case study that analyzed the economic, environmental and social viability, based on real productivity data collected between the years 2021 and 2022, in three photovoltaic systems of Distributed Generation of energy in rural properties of the municipality consistent with different levels of installed power. The research methodology consisted of analyzing the application of photovoltaic energy in rural activities corroborating with bibliographic consultations and contrasting with information provided by government entities. As a result, information regarding solar energy in Distributed Generation in Brazil was provided, highlighting the advantages and difficulties faced by photovoltaic energy in the rural sector. The case study resulted in a comparison of economic viability in the IRR, Discounted Payback, NPV and LCOE indicators, of environmental viability with an annual mitigation indicator in tons of CO2 equivalent and of the number of adult trees in reforestation, and of social viability with the Average monthly savings with approximate purchase values for goods and services for social improvement. It was concluded that the reduction in electricity costs favors the gradual replacement of equipment powered by non-renewable fuels and that the reduction in operating costs also contributes to investment in better working conditions or other social areas of the families involved, such as education, health, transportation and leisure, promoting sustainable rural development.